A randomised, double-blind, placebo-controlled study to assess the safety and efficacy of methoxyflurane for procedural pain of a bone marrow biopsy. Issue 4 (7th June 2013) - Spruyt, Odette; Westerman, David; Milner, Alvin; Bressel, Mathias; Wein, Simon
Abstract : Context: Pain during bone marrow biopsy (BMB) under local anaesthesia (LA) is reported in 70% of patients, of whom 35% rate the pain as severe. Pain is experienced during both the biopsy and the marrow aspiration. Many medical centres use conscious sedation involving benzodiazepines and/or opioids administered orally or intravenously for BMB analgesia. Methoxyflurane (MEOF) is self-administered by a handheld device (the Penthrox inhaler), which is licensed in Australia for the relief of pain associated with short surgical procedures. Objectives: To evaluate the efficacy and safety of MEOF analgesia in patients with cancer undergoing BMB. Methods: Patients received LA plus either MEOF or placebo. The primary endpoint was worst pain intensity measured with the Numerical Rating Scale. Anxiety was assessed with the State Trait Anxiety Inventory (STAI-Y-1). Patients, operators and the research nurse rated global medication performance using a 5-point Likert scale. Results: Forty-nine of the 50 patients randomised to MEOF and 48 of the 50 patients randomised to placebo effectively received the allocated intervention. Mean±SD worst pain overall was 4.90±2.07 in MEOF group and 6.0±2.24 in placebo group (p=0.011). Worst pain during the aspiration was 3.3±2.0 in MEOF group and 5.0±2.4 in placebo group (p<0.001). 49% of patients treated with MEOF rated the medication as very good or excellent compared with 16.5% of the patients treated with placebo (p=0.005). 20.4% of patients treated with MEOF had an adverse event (AE) compared with 4.2% in the placebo arm (p=0.028). All AEs were grade 1. Conclusions: MEOF was safe and performed better than placebo for analgesia in BMB procedures.